One-step process for producing prebiotic arabino-xylooligosaccharides from Brewer's spent grain employing Trichoderma species - Amorim, Cláudia (2019)
Supplementary data associated with this article can be found, in the online version, at https://doi.org/10.1016/j.foodchem.2018.07.080.